Network analysis and design - Robiah Yusof (Penerbit Kolej Universiti Teknikal Kebangsaan Malaysia, 2006)
This lab module is designed to equipped student with hand-on experience on implementing their network analysis and design knowledge and to make these techniques more obvious and expose to student.